1989
DOI: 10.1172/jci114307
|View full text |Cite
|
Sign up to set email alerts
|

Acute iron poisoning. Rescue with macromolecular chelators.

Abstract: Acute iron intoxication is a frequent, sometimes life-threatening, form of poisoning. Present therapy, in severe cases, includes oral and intravenous administration of the potent iron chelator, deferoxamine. Unfortunately, high dose intravenous deferoxamine causes acute hypotension additive with that engendered by the iron poisoning itself. To obviate this problem, we have covalently attached deferoxamine to high molecular weight carbohydrates such as dextran and hydroxyethyl starch. These macromolecular forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…For example, in individuals with iron overload, net negative iron balance could not be achieved unless the drug was given by constant chronic infusion (9). The (18).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in individuals with iron overload, net negative iron balance could not be achieved unless the drug was given by constant chronic infusion (9). The (18).…”
Section: Resultsmentioning
confidence: 99%
“…In general, DFO is not injected intravenously for two reasons. First, it is a small molecule and is eliminated rapidly through the kidney, with a plasma half-life that is less than 10 min in humans (Mahoney et al, 1989;Dragsten et al, 2000). Second, the injec- 3.…”
Section: Downloaded Frommentioning
confidence: 99%
“…D, post-treatment with six 6-mg intranasal doses of 10% DFO (n ϭ 9) compared with intranasally administered water control (n ϭ 6). p values from Student's unpaired t test with #, p Ͻ 0.10 and ‫,ء‬ p Ͻ 0.05. tion of an intravenous bolus can cause acute hypotension that is rapid and can be lethal (Mahoney et al, 1989). Subcutaneous and intramuscular injections of DFO are often associated with local injection site reactions.…”
Section: Downloaded Frommentioning
confidence: 99%
“…DFO G was found to have fewer immunosuppressive properties and to exert less enhancement of virulence of Yersinia in vivo (5). Thus, DFO G might be a favorable alternative to DFO B in clinical DFO therapy.Moreover, studies have been conducted with DFO bound to hydroxyethyl starch (HES) and have indicated that HES-DFO improves safety without interference with the iron binding efficacy of DFO (22,29,32). In accordance with these results, HES-DFO was found to significantly attenuate systemic oxidant injury, resulting in less toxicity to the lung and kidney in early sepsis (30,34).…”
mentioning
confidence: 85%